Labour market effects of the polytechnic education reform: the Finnish experience - Petri Böckerman; Ulla Hämäläinen; Roope Uusitalo (Institute for the Study of Labor (IZA), 2009)
This paper evaluates the labour market effects of the introduction of the polytechnic education system in Finland. The polytechnic reform gradually transformed former vocational colleges into polytechnics. Since the timing of the reform differed across schools, we can compare the performance of polytechnic graduates to the performance of vocational college graduates controlling for both the year and the school effects. The results are somewhat sensitive to how the selectivity issues are treated but generally suggest that both the earnings and the employment levels of post-reform graduates are higher in the field of business and administration. The effects are much smaller and usually insignificant in other fields.
urn:nbn:de:101:1-20090304706
Keywords: I21; I23; 330; Vocational education; polytechnic education; school reform; return to education; Fachhochschule; Berufsausbildung; Bildungsreform; Wirkungsanalyse; Bildungsertrag; Beschäftigungseffekt; Finnland